Potential Implementation of Payment for Ecosystem Services (PES) for Mangrove Rehabilitation in Poka Village, Ambon City - Ruban, Angela; Talakua, Eygner Gerald; Talakua, Julio Alexsandro Christo (Aquaculture Department, University of Mataram, 2025)
Mangroves have an important role in supporting community welfare through various ecosystem services. However, in July 2022 there was mangrove damage in Poka Village, which was caused by exposure to waste from pipeline leaks during bridge construction. This incident damaged a mangrove area of 1,394 m2. The absence of market value for ecosystem services means that their benefits were often overlooked in economic decision-making. For this reason, incentive schemes such as Payment for Ecosystem Services (PES), where beneficiaries compensate providers, were considered necessary to reward the role of environmental service providers. The purpose of this study was to describe the potential implementation of PES for mangrove rehabilitation. The study observed the damaged mangrove areas and interviewed 61 respondents. For data analysis, the Contingent Valuation Method (CVM) was used to obtain the value of community’s willingness to pay (WTP) for mangrove rahabilitation. The results showed that the average value of willingness to pay was IDR 39,825.40 per household per month. As a concrete step, this value could be used as the initial amount of incentives in the Payment for Ecosystem Services (PES). Providers could be established or utilize existing institutional structures at the local level. Furthermore, the provider would make monthly or quarterly reports on the use of funds, the results of activities, and the condition of the mangrove ecosystem, which could be accessed by beneficiaries. Therefore, the implementation of Payment for Ecosystem Services (PES) in Poka Village had strong prospects to encourage the sustainability of mangrove ecosystem services.